2011
DOI: 10.1142/s0218127411029045
|View full text |Cite
|
Sign up to set email alerts
|

Local Minima-Based Recurrence Plots for Continuous Dynamical Systems

Abstract: A major issue in using recurrence plots (RPs) to study dynamical systems is the choice of neighborhood size for thresholding the distance matrix that creates the plot. This is particularly important for continuous dynamical systems as temporal correlations of the trajectory might provide redundant information for recurrence analysis. We suggest an alternative procedure for creating RPs using the local minima provided by the distance profile, which approximately corresponds to the recurrence information in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The similarity threshold, ǫ, is a parameter that determines whether vectors in the phase space are identified as recurrent, i.e., as revisiting the same area of the phase space. Choosing an appropriate value for ǫ can be difficult [34] and investigating the impact of ǫ on RQA output is an active research topic [35,36]; in the present work, we use a nearest neighbor approach that does not require an explicit ǫ to be set.…”
Section: Jrqamentioning
confidence: 99%
“…The similarity threshold, ǫ, is a parameter that determines whether vectors in the phase space are identified as recurrent, i.e., as revisiting the same area of the phase space. Choosing an appropriate value for ǫ can be difficult [34] and investigating the impact of ǫ on RQA output is an active research topic [35,36]; in the present work, we use a nearest neighbor approach that does not require an explicit ǫ to be set.…”
Section: Jrqamentioning
confidence: 99%
“…Nevertheless, pitfalls and artifacts are not unusual when constructing RP such as those occurring with the wrong choice of embedding parameters or high threshold (ε). [7][8][9] Thick lines, for instance, could easily occur in continuous dynamical systems due to the temporal correlation of the phase space trajectory, and, hence causing the RP to contain redundant information. 8 Such thick lines artificially increase the number of diagonal lines and even introduce vertical lines that lead to artifacts in RQA such as an increase in DET and LAM .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Thick lines, for instance, could easily occur in continuous dynamical systems due to the temporal correlation of the phase space trajectory, and, hence causing the RP to contain redundant information. 8 Such thick lines artificially increase the number of diagonal lines and even introduce vertical lines that lead to artifacts in RQA such as an increase in DET and LAM . With regard to these thick lines, Schultz et al suggested a local minima based RP with additional threshold ε to overcome this issue and demonstrated the benefits on the Lorenz system as an example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative solution could be to use a different kind of recurrence criterion, e.g. local minima, as suggested by Schultz et al [2011].…”
mentioning
confidence: 99%